PENGEMBANGAN PERANGKAT PEMBELAJARAN BERORIENTASI ETNOMATEMATIKA BATIK NUSANTARA MATERI TRANSFORMASI GEOMETRI TERHADAP KETERAMPILAN BERPIKIR TINGKAT TINGGI - Rizkhy Permata Hartindya; Sunardi Sunardi; Nanik Yuliati (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
This research is motivated by the problem of learning mathematics in the material of geometric transformation, namely the lack of understanding of students in the concept of geometric transformation so that there are still many students who have difficulty in solving geometric transformation problems. Based on this problem, the researcher developed an ethnomathematical-oriented learning tool for Nusantara batik on the material of geometric transformation on students' higher-order thinking skills. This study aims to produce a valid, practical and effective ethnomathematics-oriented learning tool for students' higher-order thinking skills. The research method used is a mixed method, namely the Plomp development method and the experimental method. The subjects in this study were class XI students at SMK 2 Pancasila Jember, with the sample consisting of 3 classes, namely the limited trial class, the control class and the experimental class. The research instruments used include validation sheets, student activity observation sheets, implementation sheets of learning devices and student response questionnaires and data collection techniques used include observation, interviews and questionnaires. Students' higher order thinking skills were measured using a higher order thinking skills test. Data were analyzed by normality, homogeneity and One Way ANOVA using SPSS. The results showed that (1) the learning tools produced were valid, practical and effective, (2) the results of the One Way ANOVA test obtained a p-value of 0.001 (sig < 0.05) which indicates that the implementation of the developed learning tools has a significant effect. significant on students' higher order thinking skills.